Exploring the Mechanisms of Modified Bu-Shen-Yi-Qi Decoction for COPD-Related Osteoporosis Therapy via Transcriptomics and Network Pharmacology Approach - Zhong Y; Wang B; Chen W; Zhang H; Sun J; Dong J (Dove Medical Press, 2023)
Yuanyuan Zhong,1,2 Bin Wang,1,2 Wenjing Chen,1,2 Hongying Zhang,1,2 Jing Sun,1,2 Jingcheng Dong1,2 1Department of Integrative Medicine, Huashan Hospital, Fudan University, Shanghai, People's Republic of China; 2Institute of Integrated Traditional Chinese and Western Medicine, Huashan Hospital, Fudan University, Shanghai, People's Republic of ChinaCorrespondence: Jingcheng Dong; Jing Sun, Email jcdong2004@126.com; sjing0610@163.comPurpose: To investigate the effectiveness of modified Bu-Shen-Yi-Qi decoction (MBSYQ) in the treatment of osteoporosis associated with chronic obstructive pulmonary disease (COPD) and its underlying mechanisms of action.Methods: Disease targets, active ingredients and targets were predicted by TTD, CTD, DisGeNET, HERB (BenCaoZuJian as its Chinese name), and multiple-TCM databases; In addition, the screened targets were performed via the online platforms DAVID 6.8 and Metascape for GO and KEGG pathway enrichment analysis; The relationship between the MBSYQ and core targets were verified by molecular docking technique. Then we established a COPD-associated osteoporosis rat model by passive 24-week cigarette exposure. We assessed the efficacy of MBSYQ by lung histopathology assessment and distal femur/the first lumbar vertebra (L1) microstructural assay. In addition, we performed tibial RNA sequencing, which was validated by RT-PCR and Western blot.Results: Screening revealed that the 350 active compounds of MBSYQ anchored 228 therapeutic targets for COPD-related osteoporosis; KEGG pathway enrichment analysis showed that the key targets mainly regulated MAPK and PI3K/AKT signaling pathways. In vivo studies showed that MBSYQ treatment alleviated pathological alterations in lung tissue, and reversed the bone loss and microstructure damage in the femur/L1 of model rats. The RNA seq indicated that MBSYQ could upregulate genes associated with anti-oxidative stress and aerobic respiration. The GSEA analysis displayed that MAPK and PI3K/AKT pathways were inhibited by CS exposure and activated by MBSYQ.Conclusion: MBSYQ is effective in the prevention and treatment of COPD-related osteoporosis, partially achieved by improving oxygen metabolism and activating MAPK and PI3K/AKT pathways.Keywords: COPD, osteoporosis, modified Bu-Shen-Yi-Qi formulae, network pharmacology, transcriptomics